Inovasi Pembelajaran Berbasis Web dalam Implementasi Kurikulum 2013 di MA Baitul Makmur Rejang Lebong - Vera Yunita (Yayasan Darusssalam Bengkulu, 2025)
This study focuses on web-based learning innovation in the implementation of the 2013 Curriculum at MA Baitul Makmur Rejang Lebong during the Covid-19 pandemic. The government policy that requires the implementation of distance learning (PJJ) is a major challenge for schools to immediately prepare online learning methods. This study aims to answer three main questions: first, how is the learning process during the Covid-19 pandemic at MA Baitul Makmur Rejang Lebong; second, how are teachers' innovations in implementing the 2013 Curriculum; and third, how is the formation of student character in accordance with the 2013 Curriculum during the pandemic. This study uses a case study approach with a location at MA Baitul Makmur Rejang Lebong. The main data were obtained through interviews, observations, and documentation, then analyzed using data reduction techniques, data presentation, and verification through triangulation. The results of the study indicate that the online learning process at MA Baitul Makmur Rejang Lebong runs by utilizing available technology and information facilities, such as internet access, special computer rooms, and student android devices equipped with quotas. Web-based learning innovation is realized through the development of media and learning methods that support the achievement of the 2013 Curriculum. In addition, the formation of student character is carried out creatively and innovatively by each teacher, even though it is done online. Teachers use various approaches to instill character values ​​that are in accordance with the 2013 Curriculum, such as honesty, responsibility, and discipline, so that the achievement of these characters can be said to be successful. This study confirms that technological adaptation, innovative teaching methods, and creative character approaches are the keys to the successful implementation of the 2013 Curriculum in a pandemic situation.